INTEGRATIVE APPROACH IN THE EDUCATIONAL PROCESS OF HIGHER EDUCATIONAL INSTITUTIONS - Urinova Feruzakhon Uljaevna; Shokirova Mukhtasar Jakhongir kizi (Modern American Journals, 2025)
Integration is one of the promising methodological directions of modern education. This article analyzes the concepts of "integration", "pedagogical integration", their meaning, discusses the problems of integration in the educational process, the means and forms of implementing integration, and the effectiveness of the integrated pedagogical system. The essence of the integrative approach is revealed, the approaches of scientists to the topic, the goals, principles, and functions of the integrative approach are highlighted, the tasks of integrated courses are considered, and the components of the integrative approach are identified. Also, methods of implementing interdisciplinary connections are emphasized. Methods that can be used in the process of education and upbringing based on an integrated approach are described.
Keywords: Integration, pedagogy integration, integrative integration, events, integrated courses, interdisciplinary connections, interdisciplinary lessons, integrative approach, interactive forms of learning, integrative lesson.